2016
DOI: 10.4103/0253-7184.176220
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of unsafe sexual behavior among people living with human immunodeficiency virus/AIDS attending antiretroviral therapy center in Western India

Abstract: Background:As more and more people with human immunodeficiency virus (HIV) live longer and healthier lives because of antiretroviral therapy (ART), an increasing number of sexual transmissions of HIV may arise from these people living with HIV/AIDS (PLWHA). Hence, this study is conducted to assess the predictors of unsafe sexual behavior among PLWHA on ART in Western India.Materials and Methods:The current cross-sectional study was carried out among 175 PLWHAs attending ART center of a Tertiary Care Hospital i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 23 publications
2
7
4
Order By: Relevance
“…This finding was lower than a study conducted in the USA which reported 49.4% of PLWHA had unsafe sexual behavior, mainly inconsistent condom [ 38 ], in an India study in which Fifty-eight percentage of PLWHAs were practicing unsafe sex [ 11 ], a study conducted in Wakiso health center IV, Uganda (60.9%) [ 39 ] and a Nigerian study (56%) [ 40 ]. However, higher than study conducted in Jamaica, Brazil and Argentina, reported the prevalence of risky sexual practice or irregular condom use were 25%, 29% and 20%, respectively [ 41 43 ], and a study conducted in the United kingdom (UK) found that 12.8% of participants admitted to engaging in sexually risky behavior (unprotected sex in the previous 3 months with someone who was HIV-negative or of unknown HIV status) [ 44 ], and study in Togo (34.6%) [ 45 ], Nigeria (25.2%) [ 46 ], Uganda (25.9%) [ 47 ], and another a meta-analytic review conducted on Highly Active Antiretroviral Therapy and sexual risk behavior reported the median risky sexual practice among HAART attendees were 33% [ 48 ].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This finding was lower than a study conducted in the USA which reported 49.4% of PLWHA had unsafe sexual behavior, mainly inconsistent condom [ 38 ], in an India study in which Fifty-eight percentage of PLWHAs were practicing unsafe sex [ 11 ], a study conducted in Wakiso health center IV, Uganda (60.9%) [ 39 ] and a Nigerian study (56%) [ 40 ]. However, higher than study conducted in Jamaica, Brazil and Argentina, reported the prevalence of risky sexual practice or irregular condom use were 25%, 29% and 20%, respectively [ 41 43 ], and a study conducted in the United kingdom (UK) found that 12.8% of participants admitted to engaging in sexually risky behavior (unprotected sex in the previous 3 months with someone who was HIV-negative or of unknown HIV status) [ 44 ], and study in Togo (34.6%) [ 45 ], Nigeria (25.2%) [ 46 ], Uganda (25.9%) [ 47 ], and another a meta-analytic review conducted on Highly Active Antiretroviral Therapy and sexual risk behavior reported the median risky sexual practice among HAART attendees were 33% [ 48 ].…”
Section: Discussionmentioning
confidence: 65%
“…The prevalence of risky sexual practices varies by country, ranging from 23% to 58% [ 8 , 11 , 13 ]. In Ethiopia, the risky sexual practices among PLWHA receiving ART ranged from 22% to 79.8% [ 7 , 14 – 24 ], with the most prevalent factors associated with risk sexual practice being a lack of discussion about safe sex with their partner/s, an unknown partner’s serostatus, and having multiple sexual partners [ 16 18 , 22 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the current study, a similar study conducted in western India showed that those with sero-positive partners were 3 times more likely to engage in unsafe sex. 15 The possible explanation might be due to false belief that condom is not important if both of them are sero-positive. This might hasten HIV reinfection with different strains and may lead to drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with studies from Addis Ababa and western India. 11 , 15 This might indicate that individuals who felt stigmatized were afraid to disclose their status to their partner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation